Copper-mediated oxidative homocoupling and rearrangement of N-alkoxyamides: an efficient method for the preparation of aromatic esters. Issue 31 (29th July 2015) - Duan, Xiyan; Yang, Kun; Tian, Shuang; Ma, Junying; Li, Yaning; Zou, Jiao; Zhang, Dongliang; Cui, Huanqing
Graphical abstract: Abstract: N -Alkoxyamides are successfully converted into their corresponding esters in a moderate to satisfactory yields via copper-catalyzed oxidative homocoupling and Heron rearrangement. The process tolerates a wide variety of functional groups and allows the synthesis of sterically hindered ester products not readily accessible by traditional acylation chemistry. A radical-mediated pathway has been tentatively proposed for the oxidative process.